En bloc explant of silicone breast prostheses and quality of life and evolution of ASIA syndrome symptoms - Ricardo Eustachio de Miranda (Revista Brasileira de Cirurgia Plástica)
Introduction: ASIA syndrome is the abbreviation for the adjuvant-induced autoimmune syndrome, a syndrome that encompasses autoimmune diseases triggered by silicone and other substances. Evidence shows the association of silicone breast implant with ASIA syndrome. The silicone prosthesis explant is an essential resource in treating ASIA syndrome; however, there are few studies analyzing the improvement in symptoms and the quality of life that surgery can provide. Methods: Fifteen patients with ASIA syndrome who underwent breast implant prosthesis and reconstruction with mastopexy were analyzed. During the 12-month followup, they were assessed for symptom evolution and, through the Breast-Q® questionnaire, for quality of life. Results: The most common symptoms, such as myalgia, arthralgia, chronic fatigue, dry skin, and hair, were improved in more than 80% of patients operated on after 12 months of followup. There was an improvement in the quality of life after the surgical procedure when compared to the preoperative. Conclusion: Breast prosthesis explants in patients with ASIA syndrome seem to be associated with improved quality of life and decreased symptoms related to the syndrome.